Chemical reaction engineering : beyond the fundamentals - Doraiswamy, L. K. (Laxmangudi Krishnamurthy) (Boca Raton : Taylor & Francis, 2013)
'This up-to-date textbook fills a longstanding gap for graduate courses in chemical reaction engineering. It explores the interplay between transport processes and reaction kinetics, multiphase reactions and reactors, and optimization and reactor stability. The book includes a brief review of major concepts, describes chemical reaction kinetics and the effect of various factors, and addresses reactor classification and reactor design for increasingly complex situations. It helps readers to develop the facility to apply engineering analysis to a representative spectrum of industrially important reaction engineering problems'--
Includes bibliographical references and index.
Keywords: Chemical engieering; Chemical reactions